Measurement of the top quark mass from top quarks produced in proton-proton collisions at √s = 13 TeV that decay to dimuons via a J/ψ - Barends, Kevin (Department of Physics, 2023)
The top quark mass is measured using tt → lepton + J/ψ(→ µ +µ −) events, using proton-proton collision data collected by the ATLAS detector at a centre-of-mass energy of √ s = 13 TeV, during 2015-2018. The data corresponds to a total integrated luminosity of 139.0 fb−1 . This lepton + J/ψ channel is statistically limited due to the low branching ratio of the b → J/ψ → µ +µ −. The top quark mass is measured from template fits over the m(lepton,J/ψ) distribution. The top quark mass is measured to be 172.03 ± 0.76 (stat) ± 2.14 (syst) GeV.